MEKANISME PENJALURAN DALAM EKSPIR DAN IMPOR - Sugianto Sugianto (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
In the mechanism of channel activity Export and Import, If Red Channel, Green Channel, Yellow Channel and MITA is one way to prohibition of the entering at the dangerous merchandising and the minimize the numerous of smuggle. Make to a service system in custom office without intervention for the user custom office is low risk which name MITA Channel (Mitra Utama). The way of treating in channel at import service is the evidence of control which did the export duty to optimize income tax at the country, prohibition and the act of the smuggle at the user custom office.